Methylmalonic acidemia (MMA) in pregnancy: a case series and literature review. Issue 5 (8th January 2015) - Raval, Donna B.; Merideth, Melissa; Sloan, Jennifer L.; Braverman, Nancy E.; Conway, Robert L.; Manoli, Irini; Venditti, Charles P.
Abstract: Introduction: Women with inherited metabolic disorders, including those with previously life‐limiting conditions such as MMA, are reaching child‐bearing age more often due to advances in early diagnosis and improved pediatric care. Information surrounding maternal and fetal complications associated with the underlying disorders remains largely unexplored. Methods: Pregnancies affected by maternal MMA were ascertained through study 04‐HG‐0127 "Clinical and Basic Investigations of Methylmalonic Acidemia and Related Disorders" (clinicaltrials.gov identifier: NCT00078078) and via literature review. Prenatal and delivery records in study participants were reviewed. Results: Seventeen pregnancies were identified in women with isolated MMA, including three abortions, one termination, and 13 completed pregnancies [three cases with cblA (four pregnancies), four cases of mut ‐ (one cobalamin responsive, three non‐responsive), five cases with unknown type of MMA]. Seventeen percent (3/17) of the pregnancies resulted in a first trimester abortion, while 38.5 % (5/13) of the completed pregnancies resulted in preterm deliveries. A cesarean delivery rate of 53.8 % (7/13) was noted among the cohort. Fetal distress or nonreassuring fetal status was the indication for 57 % (4/7) cesarean deliveries. One patient was reported to have metabolic crisis as well as episodes of mild hyperammonemia. Malformations or adverse outcomes in the progeny were not observed. Conclusion: Although there have been a small number of pregnancies identified in women with MMA, the cumulative results suggest that the majority of pregnancies can be complicated by cesarean delivery and increased risk of prematurity. A pregnancy registry could clarify perinatal complications and define management approaches needed to ensure optimal maternal and fetal outcomes in this growing patient population.